Teologi Kerja Petani Lahan Kering: Menemukan Makna Kerja Petani Suku Atoin Meto Timor dalam Terang Ajaran Sosial Gereja - Alexius Poto Obe; Denny Firmanto (Jurnal Magistra, 2024)
This paper explores the future of work in Catholic social teaching from the encyclical Mater et Magistra to Laudato Si, with an emphasis on the development of key social documents. This paper underlines that the Church's social teaching does not aim at scientific analysis or technical solutions about work, but rather at placing the dignity and rights of workers at the center of work issues. The Atoin Meto tribe also has a deep view of work, which is reflected in the rice and corn creation myth in which Uis Neno, the Lord of the Heavens, gave plant seeds to humans. This article was studied using qualitative methods with a case study approach to the work culture of the Atoin Meto tribe and literature study. The research results present that agricultural culture is closely connected to religious cults, focusing rituals on corn and rice. Humans are presented as co-creators in their work culture, emphasizing the spiritual dimension of farming work. The unique thing is, in the culture of farming work, Atoin Meto not only build contact with nature in silence, they build communication with Uis Neno, the Lord of Heaven in and through ritual language.